1990
DOI: 10.1101/gad.4.12a.2146
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for base-pairing between mammalian U2 and U6 small nuclear ribonucleoprotein particles.

Abstract: Intramolecular and intermolecular snRNA cross-links were generated by irradiating HeLa nuclear extract with 365 nm light in the presence of the psoralen derivative AMT. After deproteinization, cross-linked RNAs were resolved by gel electrophoresis and identified as anomalously migrating species by Northern blotting. In addition to the U4/U6 snRNA cross-link, we detected an intermolecular U2/U6 cross-link, as well as several apparently intramolecular Ul, U2, and U5 cross-links. Photoreversal of the U2/U6 cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
138
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 66 publications
5
138
0
2
Order By: Relevance
“…These structures have received substantial interest in the past, as explified by the following non-exhaustive list of references covering a diverse set of animal species: Homo sapiens U1 [54], U2 [25], U4 [37], U5 [6,79], U6 [25], U11 [66,51,82], U12 [66,51,82] and U4atac [72], Rattus norvegicus U1 [37], U4 [37], U5 [37], Gallus gallus U4 [37], U5 [6], Xenopus laevis U1 [18], U2 [47], Caenorhabditis elegans U1, U2, U5, U4/U6 [84], Drosophila melanogaster U1 [54,56], U2 [56], U4 [56], U5 [56], U4atac/U6atac, U6atac/U12 [59], Bombyx mori U1 [76], U2 [75], Asselus aquaticus U1 [3], Ascaris lumbricoides U1, U2, U5, U4/U6 [70]. Large changes in snRNA structures over evolutionary time were recently reported for hemiascomycetous yeasts [50].…”
Section: Secondary Structuresmentioning
confidence: 99%
“…These structures have received substantial interest in the past, as explified by the following non-exhaustive list of references covering a diverse set of animal species: Homo sapiens U1 [54], U2 [25], U4 [37], U5 [6,79], U6 [25], U11 [66,51,82], U12 [66,51,82] and U4atac [72], Rattus norvegicus U1 [37], U4 [37], U5 [37], Gallus gallus U4 [37], U5 [6], Xenopus laevis U1 [18], U2 [47], Caenorhabditis elegans U1, U2, U5, U4/U6 [84], Drosophila melanogaster U1 [54,56], U2 [56], U4 [56], U5 [56], U4atac/U6atac, U6atac/U12 [59], Bombyx mori U1 [76], U2 [75], Asselus aquaticus U1 [3], Ascaris lumbricoides U1, U2, U5, U4/U6 [70]. Large changes in snRNA structures over evolutionary time were recently reported for hemiascomycetous yeasts [50].…”
Section: Secondary Structuresmentioning
confidence: 99%
“…In the newly formed spliceosome, a specific sequence of U5 interacts with the exon sequences at the 5' and 3' splice sites (Newman and Norman, 1991;Newman and Norman, 1992;Wyatt et al, 1992;Cortes et al, 1993;Sontheimer and Steitz, 1993), and other sequences of U4 and U6 base-pair with each other. Then, before the first step of splicing occurs, the spliceosome undergoes dynamic changes, resulting in the departure of U1 and U4, and the formation of new duplexes, including those between U2 and U6, and between U6 and the 5' splice site (Hausner et al, 1990;Datta and Weiner, 1991;Wu and Manley, 1991;Yean and Lin, 1991;Madhani and Guthrie, 1992;Sawa and Abelson, 1992;Wassarman and Steitz, 1992;Lesser and Guthrie, 1993;Nilsen, 1994). The resulting conformational changes lead to the formation of the active spliceosome (complex B2), triggering the first step of splicing, where the bulged-out branch point adenosine nucleophilically attacks the phosphate at the 5' splice site.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct spliceosomal systems have co-existed in eukaryotic cells since at least the divergence of the plant and animal kingdoms (reviewed in Tarn & Steitz, 1997)+ These two systems act on pairs of mutually incompatible splice sites flanking pre-mRNA introns in eukaryotic nuclear genomes+ The large majority of introns in all known organisms are spliced by a wellstudied pathway requiring the function of the small nuclear RNAs U1, U2, U4, U5, and U6, as well as a large number of additional proteins+ In this pathway, multiple RNA-RNA interactions have been demonstrated to form between the splice site sequences and the snRNAs and between various snRNAs in the spliceosome (reviewed in Nilsen, 1998)+ One of the earliest interactions takes place between the 59 end of U1 snRNA and the 59 splice site via base pairing (Zhuang & Weiner, 1986;Seraphin et al+, 1988;Siliciano & Guthrie, 1988)+ A second base pairing interaction takes place between the sequence in the intron surrounding the site of branching and a region of U2 snRNA (Parker et al+, 1987;Wu & Manley, 1989;)+ Following these initial recognition events, a complex of U4, U5, and U6 snRNPs joins the nascent spliceosome and the combined assemblage undergoes several structural rearrangements+ During this portion of the spliceosome assembly process, the extensive base pairing between U4 snRNA and U6 snRNA is disrupted so that U6 snRNA can participate in base pairing to U2 snRNA (Hausner et al+, 1990;Datta & Weiner, 1991;Wu & Manley, 1991;Madhani & Guthrie, 1992)+ In addition, an adjacent sequence in U6 snRNA forms base pairs to the 59 splice site, which displaces U1 snRNA from the complex (Kandels- Lewis & Seraphin, 1993;Lesser & Guthrie, 1993;Hwang & Cohen, 1996)+ U5 snRNP interacts with exon sequences near the 59 and 39 splice sites, but apparently without substantial sequence specificity (Wyatt et al+, 1992;Sontheimer & Steitz, 1993;Newman, 1997)+ Thus, 59 splice site activation appears to be at least a two-step process in which U1 snRNP, probably in cooperation with additional factors, specifies the 59 splice site followed by U5 and U6 snRNP interactions that activate the site for reaction+ A striking feature of these RNA-RNA interactions is their apparent high degree of conservation throughout eukaryotic phylogeny+ These interactions have been studied in both yeast and human systems in vivo and in vitro by a variety of techniques (see Moore et al+, 1993 andNilsen, 1998 for reviews)+ These studies have demonstrated the stepwise assembly of the spliceosome and the roles of sequence elements in the...…”
Section: Introductionmentioning
confidence: 99%